2015
DOI: 10.1002/bdra.23342
|View full text |Cite
|
Sign up to set email alerts
|

First approximation to congenital malformation rates in embryos and hatchlings of sea turtles

Abstract: Olive ridleys seem more prone to the occurrence of congenital malformations than the other two species. Whether the observed malformation levels are normal or represent a health problem cannot be currently ascertained without long-term assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 81 publications
3
60
0
2
Order By: Relevance
“…Developmental anomalies are associated with extreme temperatures in freshwater turtle and mammalian embryos (Edwards ; Packard & Packard ), but although studies are limited in number, no strong association has been demonstrated for marine turtles (Bárcenas‐Ibarra et al . ). Hewavisenthi and Parmenter (2001) showed a significant influence of temperature on carapace scute anomalies in the flatback turtle ( Natator depressus ); however, these observations were detected at the lower end of the thermal tolerance limits.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Developmental anomalies are associated with extreme temperatures in freshwater turtle and mammalian embryos (Edwards ; Packard & Packard ), but although studies are limited in number, no strong association has been demonstrated for marine turtles (Bárcenas‐Ibarra et al . ). Hewavisenthi and Parmenter (2001) showed a significant influence of temperature on carapace scute anomalies in the flatback turtle ( Natator depressus ); however, these observations were detected at the lower end of the thermal tolerance limits.…”
Section: Discussionmentioning
confidence: 97%
“…Despite this limited available data, high temperatures are still hypothesized to promote the occurrence of congenital malformations (Bárcenas‐Ibarra et al . ). We show that the gene tgm3 , which encodes for a protein associated with epidermis development in mammalian embryogenesis (Zhang et al .…”
Section: Discussionmentioning
confidence: 97%
“…Cyclopia has also been reported in 1 olive ridley sea turtle ( Lepidochelys olivacea ) embryo from Sinaloa, Mexico. The embryo did not hatch, although other siblings within the same nest hatched normally [Bárcenas-Ibarra et al, 2015].…”
Section: Hox Genes Teratogenesis and Environmental Influencementioning
confidence: 98%
“…25 The prevalence of congenital malformations in embryos and hatchlings of sea turtles ranges from 0.2% to 2%, with the highest rate occurring in the olive ridley. 5 A wide variety of isolated and multiple congenital malformations have been reported in this species, 5 but there were no reports of SRS until it was observed in embryos from a Mexican Pacific hatchery. Thus, the purpose of the present study was to characterize the morphology and determine the overall prevalence of schistosomus reflexus in olive ridley sea turtles in this specific nesting beach in which conservation programs have been running uninterruptedly for 39 years and to establish the potential impact of this syndrome in the population.…”
mentioning
confidence: 99%
“…1,32 The most important nesting areas for this species are located in the Eastern Pacific coast; 28,32 nesting sites in Mexico extend from the southernmost tip of the Baja California peninsula to the coastline of Chiapas state. 28 A variety congenital malformations have been previously reported in olive ridleys 5 but not schistosomus reflexus syndrome (SRS). SRS is a rare and lethal congenital malformation occurring primarily in ruminants, mostly cattle.…”
mentioning
confidence: 99%